A Review of Wearable Sensor Systems for Hand Transmitted Vibration (HTV) Applications - Abang Mohamad, Aizuddin; N. A. A., Jalil (AIP Publishing, 2022)
Hand-transmitted vibrations (HTV) are a common occurrence in everyday human life. The vibration exposure differs by individuals and presents a major health risk especially in industries that require manual operation of rotating power tools. Humans can develop symptoms known as hand arm vibration syndrome (HAVS) if this exposure is excessive and unmonitored. This review paper aims to summarize the recent advancements in the field of wearable sensor systems specifically for hand transmitted vibration applications. Available systems are compared, and limitations are highlighted. Aspects of the enabling technologies that allow for the increased significance of wearable systems such as the sensor technology and wireless communication technology are discussed. This paper also proposes a conceptual model of a smart wearable system for hand-transmitted vibration measurements. It is predicted that the wearable sensor technology will transcend measurement and monitoring purposes and will be an important component in hand vibration control applications via cloud-computing and Internet of Things (IoT) technologies.